2021
DOI: 10.1007/s11101-021-09762-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics: towards acceleration of antibacterial plant-based leads discovery

Abstract: The wide and not yet fully uncovered potential of plant secondary metabolites make plants a rich source of drug leads. Metabolomics enables the study of the metabolic perturbations taking place in bacterial cells under the influence of plant-based bioactive molecules. It reveals the changes in metabolic pathways within bacteria, reflecting the reprogramming of the biochemical networks. From this point of view, metabolomics is valuable in understanding the alteration of cell functions when bacteria are subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 72 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Metabolomics analyses gave some insight into the possible factors that could inhibit C. sakazakii. Untargeted metabolomics and PCA have been used to screen for potential bioactive molecules from plants and evaluate the metabolic changes of foodborne pathogens post-exposure to biochemical or physical treatments (Maifiah et al, 2017;Tian et al, 2018;Sieniawska and Georgiev, 2022). In this study, the PCA biplot revealed differences in metabolite profile within the SHIME compartments that may be generally associated with C. sakazakii levels.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics analyses gave some insight into the possible factors that could inhibit C. sakazakii. Untargeted metabolomics and PCA have been used to screen for potential bioactive molecules from plants and evaluate the metabolic changes of foodborne pathogens post-exposure to biochemical or physical treatments (Maifiah et al, 2017;Tian et al, 2018;Sieniawska and Georgiev, 2022). In this study, the PCA biplot revealed differences in metabolite profile within the SHIME compartments that may be generally associated with C. sakazakii levels.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are promising antimicrobials that can influence bacterial cells on different metabolic and functional levels ( Sieniawska and Georgiev, 2022 ). They usually have multiple cellular targets other than synthetic antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of TQ on bacterial cells can be monitored by metabolomics, which detects a large number of analytes and reflects the complexity of metabolic alterations. The significantly changed metabolites indicate targeted metabolic pathways and thus reflect the direct or indirect influence of the test compound on bacteria ( Sieniawska and Georgiev, 2022 ). To get insight into the regulation of bacteria’s response to stress factors, a more comprehensive gene-metabolite approach is required ( Sieniawska and Georgiev, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation